A rare case of invasive fungal sinusitis by co-infection of two fungi in a post COVID-19 patient: a case report - Chungath, Timna; Kumar, Deepak Dileep; Mathew, Shalu Susan; Paul, Jijo (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Invasive fungal rhinosinusitis is a disease of the paranasal sinuses and nasal cavity that typically affects immunocompromised patients in acute fulminant form. Early symptoms can often mimic rhino sinusitis while late symptoms can cause significant morbidity and mortality. With early diagnosis and treatment can increase the patient survival. This case report is of 73 years old diabetic post COVID-19 patients. The patient presented to us was having severe headache and facial pain confined to left side cheek area with loosening of teeth. The patient underwent nasal cavity and biopsy from the maxillary sinus (left side) under local anaesthesia, which confirmed the diagnosis of invasive fungal sinusitis suggestive of co-infection by 2 fungi, aspergillus flavus and mucor. Further, the patient underwent surgical debridement and started on liposomal amphotericin B and patient improved significantly.